Evidence for elevated alkalinity in the glacial Southern Ocean - Rickaby, R; Elderfield, H; Roberts, N; Hillenbrand, C; Mackensen, A (2010)
An increase in whole ocean alkalinity during glacial periods could account, in part, for the drawdown of atmospheric CO2 into the ocean. Such an increase was inevitable due to the near elimination of shelf area for the burial of coral reef alkalinity. We present evidence, based on downcore measurements of benthic foraminiferal B/Ca and Mg/Ca from a core in the Weddell Sea, that the deep ocean carbonate ion concentration, [CO32-], was elevated by ∼25 μmol/ kg during each glacial period of the last 800 kyr. The heterogeneity of the preservation histories in the different ocean basins reflects control of the carbonate chemistry of the deep glacial ocean in the Atlantic and Pacific by the changing ventilation and chemistry of Weddell Sea waters. These waters are more corrosive than interglacial northern sourced waters but not as undersaturated as interglacial southern sourced waters. Our inferred increase in whole ocean alkalinity can be reconciled with reconstructions of glacial saturation horizon depth and the carbonate budget if carbonate burial rates also increased above the saturation horizon as a result of enhanced pelagic calcification. The Weddell records display low [CO32-] during deglaciations and peak interglacial warmth, coincident with maxima in percent CaCO3 in the Atlantic and Pacific oceans. Should the burial rate of alkalinity in the more alkaline glacial deep waters outstrip the rate of alkalinity supply, then pelagic carbonate production by the coccolithophores at the end of the glacial maximum could drive a decrease in ocean [CO32-] and act to trigger the deglacial rise in pCO2. Copyright 2010 by the American Geophysical Union.